Cardiac Tamponade Related to a Large Pericardial Mass in a Female with Juvenile Idiopathic Arthritis. Issue 2 (March 2023) - Wirth, Scott H.; Pater, Colleen M.; Wells, Dennis; Tretter, Justin T.; Hahn, Eunice; Morales, David L. S.; Powell, Adam W.
We report the case of a young female with juvenile idiopathic arthritis presenting with cardiac tamponade secondary to an unusual pericardial mass. Pericardial masses are typically incidental findings. In rare circumstances they can cause compressive physiology warranting urgent intervention. She required surgical excision which revealed a pericardial cyst encapsulating a chronic solidified hematoma. Though certain inflammatory disorders are associated with myopericarditis, to our knowledge this is the first reported case of a pericardial mass in a well-controlled young patient. We theorize her immunosuppressant therapy resulted in hemorrhage into a pre-existing pericardial cyst, suggesting the need for further follow-up in those on adalimumab therapy.